Outcome and prognostic factors of radiation therapy for medulloblastoma - Rieken, Stefan; Mohr, Angela; Habermehl, Daniel; Welzel, Thomas; Lindel, Katja; Witt, Olaf; Kulozik, Andreas; Wick, Wolfgang; Debus, Jürgen; Combs, Stephanie E. (International journal of radiation oncology, biology, physics, 2011)
Purpose - To investigate treatment outcome and prognostic factors after radiation therapy in patients with medulloblastomas (MB). - Methods and Materials - Sixty-six patients with histologically confirmed MB were treated at the University Hospital of Heidelberg between 1985 and 2009. Forty-two patients (64%) were pediatric (≤18 years), and 24 patients (36%) were adults. Tumor resection was performed in all patients and was complete in 47%. All patients underwent postoperative craniospinal irradiation (CSI) delivering a median craniospinal dose of 35.5 Gy with additional boosts to the posterior fossa up to 54.0 Gy. Forty-seven patients received chemotherapy, including 21 in whom chemotherapy was administered before CSI. Statistical analysis was performed using the log-rank test and the Kaplan-Meier method. - Results - Median follow-up was 93 months. Overall survival (OS) and local and distant progression-free survival (LPFS and DPFS) were 73%, 62%, and 77% at 60 months. Both local and distant recurrence predisposed for significantly reduced OS. Macroscopic complete tumor resection, desmoplastic histology and early initiation of postoperative radiation therapy within 28 days were associated with improved outcome. The addition of chemotherapy did not improve survival rates. Toxicity was moderate. - Conclusions - Complete resection of MB followed by CSI yields long survival rates in both children and adults. Delayed initiation of CSI is associated with poor outcome. Desmoplastic histology is associated with improved survival. The role of chemotherapy, especially in the adult population, must be further investigated in clinical studies.